Mutu Pelayanan Kesehatan Terhadap Tingkat Kepuasan Pasien - Yunike Yunike; Indrawati Aris Tyarini; Sova Evie; Hasni Hasni; Dwi Yogyo Suswinarto (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Complete health care is an important factor in achieving patient satisfaction. With the increase in people's living standards, so do the increasing demands of the community for quality health. This study aims to determine the quality of health services on the level of patient satisfaction. The quantitative research method uses a cross-sectional design with accidental sampling sample techniques totaling 66 respondents. The results of statistical analysis using the chi-square test obtained a value of p = 0.00. It can be concluded that there is a relationship between embodiment, reliability, reassurance, responsiveness and empathy for patient satisfaction. Quality health care is an important factor in achieving patient satisfaction. Patient satisfaction is the level of feeling the patient feels that arises as a result of the performance of health services obtained after the patient compares it to exceed what he expected